Idiopathic thrombocytopenic purpura during pregnancy and delivery: a case report - Skoczyński, Mariusz; Kwaśniewska, Anna (Menopause Review/Przegląd Menopauzalny, 2010)
Thrombocytopenia is second to anaemia as the most common hematologic abnormality during pregnancy. It may result from a variety of causes. Appropriate diagnosis and management are important due to the risk of maternal and neonatal haemorrhage. Gestational or incidental thrombocytopenia with mild declining platelet count is not associated with adverse pregnancy outcomes. A small number of patients suffering from immune thrombocytopenia purpura need specific therapies, which if employed promptly, may improve pregnancy outcomes. We describe the case of a 27-year--old pregnant woman with immune thrombocytopenia purpura. The article focuses on the successful management of pregnancy and the way of the delivery as well.